Organizational Values And Its Relationship With Organizational Commitment Of The Staff Of The Directorate Of Youth And Sport Of M'sila - salem, layachi (sports creativity, 2025)
This study aims to find out the relationship between the link organizational values and Organizational commitment of the staff of the Directorate of youth and sport of M'sila The most important results : - There is a correlation between the configured values for organizational culture (strength, elite, reward, system) and the Organizational commitment of the staff of the Directorate of youth and sport of M'sila. - There is a correlation between the configured values for organizational culture (efficiency, justice, teams work, effectiveness) and Organizational commitment of the staff of the Directorate of youth and sport of M'sila.